"Hot Collecting Off the Record: Ralph J. Gleason's Start in Music Journalism". (3rd May 2020) - Armstrong, Don
ABSTRACT: Ralph J. Gleason (1917–75) was one of the most influential writers on jazz and popular music from the 1930s until his death. Because of his significance to music journalism, Gleason's contributions to music writing have been studied in numerous articles and books, yet his formative years remain understudied. This article will take a closer look at a wide array of early experiences, and will show how they shaped Gleason's journalistic persona, music aesthetic, and political activism. The accounts of Gleason's early years focus exclusively on two events: his teenage jazz conversion in Chappaqua, New York, and his initiation into record collecting at Columbia University during the nascent years of the Swing Era. While these incidents were deeply formative, they were part of larger pattern of experiences that shaped Gleason in this critical period.